PRESERVICE CHEMISTRY TEACHERS’ CHEMICAL LITERACY BASED ON PISA AND TIMSS RESULTS FOR INTERNATIONAL AND INDONESIAN STUDENTS (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
PISA and TIMSS results have been used as a basis for educational reform, but unfortunately, teachers’ understanding of PISA and TIMSS tests is rarely investigated. We evaluated 149 sophomore preservice chemistry teachers’ achievement in TIMSS and PISA-like test. As a way to reflect on TIMSS and PISA results, we compared preservice chemistry teachers’ achievement to PISA and TIMSS results for Indonesia and the international students. Results suggested that, to a certain degree, preservice chemistry teachers have a better chemical literacy than Indonesian students and a somewhat similar chemical literacy with international students.
Keywords: preservice chemistry teachers; chemical literacy; PISA; TIMSS